THE 125 MODULAR BRIDGES PROJECT TO PERU. Issue 5 (9th March 2020) - André, António; Ferraz, Inês; Coelho, Hugo; Fernandes, José; Pacheco, Pedro
Abstract: This paper presents the general aspects that were considered on the design phase of 125 modular steel bridges developed in Portugal for delivery to a department of the Peruvian Ministry of Transport and Communications. Some of the main features of manufacturing, pre‐assembly and containerization in Turkey are also presented. Some of the tests performed on the floor modules are also introduced, namely the load tests until failure, the fatigue tests, the durability validation tests of the hot deep galvanized and the antiskid coating. The main results of the tests are also discussed, and their conclusions presented.